21st Century Cooperation Regional Public Goods, Global Governance, and Sustainable Development - Estevadeordal, Antoni; Goodman, Louis W. (Taylor & Francis, 2017)
This edited volume explains the importance of regional public goods (RPGs) for sustainable development and shows why they are particularly important in the context of 21st-century international relations. By presenting a new and original data set and by presenting original essays by renowned scholars, this book lays the foundation for what will become an increasingly important focus for both economic development and international relations as well as for their intersection. This book contains four parts. The first introduces the core issues and concepts that are explored throughout the book as well as a new and original data set on regional public goods (RPGs). The second part further develops specific concepts important for understanding 21st-century RPGs: regional leadership, alliances, networks, and outcomes. The third part examines how cooperation takes place worldwide for a range of important RPGs. The fourth part discusses how public goods are produced in specific regions, stressing that each region has a distinct context and that these contexts overlap in a decentered "multiplex" manner.